Poisoning by Street Food, Group Kitchen - Ba Le Huy; Hoan Nguyen Xuan; Phong Nguyen Tan; Thanh Le Minh (Food Toxicology: Theory, Practice and Resolve in Vietnam, 2022)
The basic content of chapter 17 is to state the cause of human poisoning by eating poisonous Animal Contains toxic, Noxious. This chapter covers the following topics: REMOVAL MEASURES FOR FOOD POSSIBILITY AND POSSIBILITY Unsafe food can lead to more than 200 diseases, from diarrhea to cancer. Among them, diarrhea is the most common disease, causing 550 million illnesses and 230,000 deaths each year. It is estimated that nearly 1 in 10 people get sick from eating unsafe food, leading to 420,000 deaths each year, equivalent to 33 million healthy life years (DALYs). Children account for 40% of food poisoning cases, of which 125,000 children die each year. (according to WHO as of 2015). There are two main factors that make food unsafe: biological agents (viruses, bacteria, parasites, prions) and chemical agents (poisons). Bacteria: Salmonella, Campylobacter, and Enterohaemorrhagic Escherichia coli are the most common bacteria that make food unsafe, with symptoms of headache, nausea, vomiting, abdominal pain, and diarrhea. For ex: Salmonella: found in eggs, poultry, products of animal origin. Campylobacter: raw or undercooked milk, poultry and drinking water. Enterohaemorrhagic Escherichia coli: unpasteurized milk, undercooked meat and fresh fruits and vegetables. Listeria: lead to miscarriage, or infant death. The frequency of encountering this bacterium is relatively low, but the consequences can be serious and even fatal, especially in infants, children and the elderly. Listeria is found in unpasteurized milk and packaged foods and can grow at cold temperatures. Vibrio cholera (cholera). In addition, the widespread overuse of antibiotics in humans and animals not only makes the treatment ineffective, but also can lead to the development of drug-resistant strains of bacteria. These resistant strains of bacteria enter food through animals (eg, Salmonella pine chicken). Virus: Norovirus infection is characterized by nausea, vomiting, diarrhea, and abdominal pain. The hepatitis A virus can cause long-lasting liver disease and is spread through raw and undercooked seafood. 3-Heavy metals such as lead, cadmium and mercury cause nerve and kidney damage. Contamination by heavy metals in food occurs mainly due to air, water and soil pollution. Solutions: To solve the problem of food safety requires good coordination between the government, producers and consumers: Policy makers; Food suppliers and consumers: Assessing the level of food safety is a very difficult and complex job, requiring persistence and reasonable techniques. Nowadays, people often